Nature of Injuries in Recent Combat Scenario at Shree Birendra Hospital: A Retrospective Study - KC, Bachhu Ram; Hamal, B K; Joshi, Amit (Medical Journal of Shree Birendra Hospital, 2002)
Nature of Injuries in Recent Combat Scenario at Shree Birendra Hospital: A Retrospective Study